An Approach of Hardware and Software Partitioning for the Wearables Design with Limited Reconfigurable Hardware Resources - Guimarães, Rodolfo Labiapari Mansur; Oliveira, Ricardo Augusto Rabelo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
The technologies in microelectronic, sensors and mobile communication have been continuously improved as information becomes more needed. They become a stimulus for the development of intelligent and connected systems as embedded systems, IoTs or wearables, seen by the rapid growth of theses for the market. However, still with difficulty to satisfy the requirements of performance increase and reduction of the energy consumption of the various autonomous modern applications. Performance analysis in the use of FPGA with hardware partitioning for embedded systems has been strongly addressed by the academic community. Also, there are not researches that address the partitioning problem for wearable systems. This work has as objective the enhancement of performance of wearable computers devices in reconfigurable hardware, targeting optimizations in the use of resources and reducing the energy consumption, using hardware and software partitioning. The results show that it is possible to obtain higher performance in wearable systems using FPGA platform only with the relocation of candidates algorithms in hardware.